Physical and wear properties of aluminium matrix composite reinforced with PSAC and slag fabricated via powder metallurgy - Zamri, Yusoff (Universiti Malaysia Perlis (UniMAP), 2014)
A study of physical and wear properties were carried out on pure aluminium reinforced with biomass by product such as palm shell activated carbon (PSAC), slag and PSAC/slag particles. Hybrid and unhybrid aluminium composites containing 5-20 wt.% of reinforcements were fabricated via powder metallurgy. Physical properties of as-sintered specimen such as density, apparent porosity and macro-hardness are determined. The wear rate was measured by pin-ondisc technique while debris, worn and sub-surfaces have been analysed by using SEM and EDX. Dry sliding experiments were conducted in air at room temperature using a pin-on-disc self-built attached to polisher machine. The disc which acted as the mating surface material was made of mild steel. The influence of the applied load was investigated under a constant sliding velocity of 0.58 m/s with the applied loads at 3 N, 11 N and 51 N. Result appears that the slag/Al unhybrid composite had the highest values of bulk density and macrohardness. The PSAC/slag/Al hybrid composite gave intermediate values and the PSAC/Al unhybrid composite gave the lowest values. Porosity of PSAC/Al unhybrid composite was the highest, slag/Al unhybrid composite was lowest and PSAC/slag hybrid composite was the intermediate comparatively. Dry wear sliding showed the mass loss of composites relative to the aluminium was reduced significantly when the addition of reinforcement up to 20 wt.% slag for Al/slag composite, up to 15 wt.% PSAC/slag for hybrid composite and up to 10 wt.% PSAC for Al/PSAC composite. The wear resistance of Al/PSAC composites relative to the aluminium was improved significantly at a load up to 11 N but for Al/slag and Al/PSAC/slag composites relative to the aluminium was improved significantly at load up to 51 N. The cumulative wear rate of the PSAC/Al unhybrid composite decreased when the PSAC content less than 10 wt.% PSAC and increased when PSAC content more than 10 wt.%. The optimum content of PSAC was found to be 10 wt.% in order to achieve optimum wear resistance. The cumulative wear rate of the PSAC/slag/Al hybrid composite decreased when the PSAC/slag content less than 15 wt.% and increased when PSAC/slag content more than 15 wt.%. The optimum content of PSAC/slag was found to be 15 wt.% in order to achieve optimum wear resistance. The cumulative wear rate of the slag/Al unhybrid composite decreased drastically when the slag content less than 10 wt.%. SEM micrograph of 10 wt.% PSAC/Al composite showed carbon film smeared on the worn surface acting as self lubrication and improved wear resistance. However, SEM micrograph of 20 wt.% slag/Al composite showed the presence of fine debris as third body that acting as separator between specimen and mating surface. This third body reduced direct interaction and improved wear resistance. SEM micrograph of 7.5 wt.% PSAC/7.5 wt.% slag/Al hybrid composite showed discontinuous smear debris particles present at contact of wear surface and improved wear resistance.